PWE-020 Corticosteroid Dose Reduction with Vedolizumab Treatment of Crohn's Disease. (17th August 2016) - Loftus, E; Siegel, C; Panaccione, R; Sandborn, W; Smyth, M; James, A; Xu, J; Abhyankar, B
Abstract : Introduction: Corticosteroids (CS) can effectively induce remission of Crohn's disease (CD), but serious side effects prohibit long-term use. Vedolizumab (VDZ) maintenance therapy resulted in a significantly higher percentage of patients with CS-free remission at week 52 versus placebo (PBO) in the GEMINI 2 study of moderately to severely active CD. 1 Methods: In GEMINI 2, patients who responded to VDZ induction therapy at week 6 were re-randomised to PBO or VDZ for 46 weeks. From week 6 onward, patients with clinical response began a CS tapering regimen. With exploratory and post hoc analyses, we characterised CS dose reductions following VDZ therapy in the population of patients on stable CS doses (≤30 mg/day prednisone or equivalent) at baseline (week 0). Median CS dose over time, change from baseline CS dose, and CS-free status at week 52 were summarised overall and by tumour necrosis factor antagonist (anti-TNF) treatment (naïve or failure) history. Results: At week 52, 68% of patients with baseline CS use decreased their CS dose with VDZ treatment compared with 62% with PBO (Table ). The median CS dose in either treatment group (VDZ or PBO) at week 52 was 5 mg/day. Higher percentages of patients (overall and anti-TNF-naïve) required CS doses of ≤7.5 mg/day with VDZ versus PBO at week 52 (Table ). In anti-TNF-naïve patients, the median CS dose at week 52 was 2.7 mg/day with VDZ and 5.0 mg/day with PBO. At week 52, higher percentages of VDZ-treated patients were CS- free for 90 or 180 consecutive days than PBO-treated patients. Conclusion: VDZ maintenance therapy was associated with numerically higher percentages of CS-free patients at week 52 and patients who were CS-free for 90 or 180 days than PBO. Interpretation of these post hoc analyses, including the degree of dose reduction, is limited by differing initiation weeks for CS tapering per patient and small sample sizes. Reference: 1 Sandborn WJ, et al . N Engl J Med . 2013;369 :711–721; NCT00783692 . Disclosure of Interest: E. Loftus Jr Grant/research support from: AbbVie, Janssen, UCB, Takeda, Pfizer, GSK, Amgen, BMS, Genentech, Robarts Clinical Trials, Gilead, Receptos, Consultant for: AbbVie, Janssen, UCB, Takeda, Immune Pharmaceuticals, Celgene, MedImmune, Theradiag, Genentech, Seres Health, Sun Pharmaceuticals, BMS, C. Siegel Grant/research support from: AbbVie, Janssen, Salix, Takeda, UCB, Consultant for: AbbVie, Amgen, Janssen, Lilly, Pfizer, Takeda, UCB, Speaker bureau with: AbbVie, Janssen, Takeda, R. Panaccione Grant/research support from: Abbott, and UCB Inc, Consultant for: Abbott, Biogen, Axcan Pharma Inc, BMS, Centocor Inc, Chemocentryx, Ferring, Genentech Inc, Lippincott Williams & Wilkins, Medscape, Osiris Therapeutics, Inc, Novartis, Genentech Inc, Elan Pharmaceuticals, Inc, UCB, W. Sandborn Grant/research support from: Janssen, AbbVie, Pfizer, Amgen, Genentech, Consultant for: Janssen, AbbVie, Pfizer, Amgen, Genentech, Takeda, Speaker bureau with: AbbVie, Takeda, M. Smyth Employee of: Takeda Development Centre Europe Ltd, London, UK, A. James Employee of: Takeda Development Centre Europe Ltd, London, UK, J. Xu Employee of: Takeda Pharmaceuticals International Co, Cambridge, Massachusetts, USA, B. Abhyankar Employee of: Takeda Development Centre Europe Ltd, London, UK